Clinical characteristics and risk profile of patients with atrial fibrillation with mid-range ejection fraction, insights from the Polish part of EORP-AF Long-Term General Registry. (25th November 2020) - Marchel, M; Tyminska, A; Ozieranski, K; Budnik, M; Wancerz, A; Massler, E; Tscheinig, O; Peller, M; Lodzinski, P; Kalarus, Z; Lenarczyk, R; Grabowski, M; et al.
Abstract: Background: Atrial fibrillation (AF) comprises a wide range of patients (pts), from those with preserved to those with reduced left ventricular ejection fraction (LVEF). According to 2016 ESC guidelines, pts with LVEF in the range of 40–49% represent a "grey area", which is defined as heart failure with mid-range ejection fraction (HFmrEF). Not much is known about the clinical characteristics of AF pts with mid-range ejection fraction. Purpose: To determine the potential differences in the clinical characteristics, risk profile, and the outcomes of AF with moderate systolic dysfunction, measured by LVEF. Methods: The EURObservational Research Programme on AF (EORP-AF) Long-Term General Registry analyzed consecutive AF patients who have presented to cardiologists in 250 centers from 27 European countries, including 25 centers from Poland. We analyzed data collected at baseline and at a 1-year follow-up visit from 568 Polish patients included in 25 Polish centers in the years 2013–2016. Pts were divided into three groups based on LVEF: the preserved LVEF (pEF) group (LVEF ≥50%), the mid-range LVEF (mrEF) group (40–49%), and the reduced LVEF (rEF) group (<40%). Results: 117/568 pts with rEF represented 20, 6%, 105/568 mrEF 18, 5% and 346/568 pEF 60, 9% of the whole analyzed group. With regard to the most typical risk factors, the mrEF population appeared between rEF and pEF, presenting a moderate risk profile with the exception of hypertension, which was the most common in the mrEF group. While permanent AF was the most common in the rEF group and paroxysmal in the pEF pts, pts with mrEF had a higher rate of long-lasting persistent AF. Taking into account the risk factors profile, surprisingly, pts with AF and mrEF more often presented with dyspnea/shortnes of breath (mrEF 38, 1% vs. rEF 18, 8% vs. pEF 22, 5%; p=0, 001) and fatigue (mrEF 38, 1% vs. rEF 23, 9% vs. pEF 25, 4%; p=0, 025). AF pts with mrEF also had the highest thrombo-embolic risk estimated with the CHA2DS2-VASc score (mrEF 4 [2–5], n=105; rEF 3 [2–5], n=117, pEF 3 [2–4], n=346, p=0.005). However, this did not translate into the highest number of thromboembolic events after one year which did not significantly differ (mrEF 10.5%, rEF 15.4%, pEF 11.3%, p=0.30) between the three groups. Conclusions: The risk factor profile of AF pts with mrEF was milder than for those with rEF and more severe than for pEF pts. AF pts with mrEF more often presented HF symptoms. Their estimated thrombo-embolic risk was higher but the number of events in the one year follow-up did not significantly differ between groups. Funding Acknowledgement: Type of funding source: None